Nutritional Improvement of Palm Oil Fronds for Ruminant Feedstuffs Using a Local Biotechnological Approach - Astuti, T.; Amir, Y.; Irdawati; Santoso, U. (Pakistan Journal of Nutrition, 2016)
This study aimed to evaluate the nutrient contents of palm fronds fermented with microorganisms derived from the rumen contents, feces and urine of local cows. The study was conducted using a completely randomized, two factorial 2 x 3 design and three replications for each treatment. Factor A was the length of incubation (A1 = 7 days and A2 = 14 days) and factor B was the type of medium (B1 = rumen contents, B2 = cattle feces and B3 = cattle urine). The observed variables were the dry matter, organic matter, crude protein and crude fiber content and the digestibilities of the dry matter and organic matter in the fermented palm fronds. The experimental results revealed that fermentation reduced the dry matter, organic matter and crude fiber content (p